2011
DOI: 10.1111/j.1540-8175.2011.01449.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity on Left Ventricular Geometry and Function in Pediatric Patients after Successful Aortic Coarctation Repair

Abstract: Our study shows that obesity in successfully treated CoA children, has an additional negative effect on BP, LV mass, and cardiac function. These findings are of particular concern, since life expectancy in CoA patients is limited mainly by atherosclerosis, and all the obesity-associated abnormalities found are harbingers of higher cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Shang et al reported increased LVM and decreased myocardial deformation in hypertensive CoA patients compared to healthy controls 23 . According to Salva et al, 24 2D‐STE analysis on obese and lean young patients revealed abnormal myocardial deformation properties along longitudinal, radial, and circumferential planes in the obese CoA patients. However, there was no obesity among our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Shang et al reported increased LVM and decreased myocardial deformation in hypertensive CoA patients compared to healthy controls 23 . According to Salva et al, 24 2D‐STE analysis on obese and lean young patients revealed abnormal myocardial deformation properties along longitudinal, radial, and circumferential planes in the obese CoA patients. However, there was no obesity among our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity leads to an increase in both total and central blood volume, resulting in elevated cardiac output (CO). This elevation in CO is primarily due to an increase in left ventricular (LV) stroke volume and a reduction in peripheral vascular resistances [19,23]. Moreover, severely obese individuals commonly exhibit heightened oxygen consumption [24].…”
Section: Impact On Cardiac Hemodynamicsmentioning
confidence: 99%
“…The impact of overweight and obesity is particularly critical in individuals with pre-existing heart conditions, such as children with CHD, as obesity s adverse effects on the cardiovascular system may exacerbate existing issues [18,19]. A recent review highlighted obesity and overweight prevalence in children with CHD reaching up to 22% and 36%, respectively [20].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Longitudinal strain has been validated to evaluate myocardial deformation in patients with CoA; circumferential strain and radial strain, on the other hand, have not shown so consistent results. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] However, data provided in the literature are still conflicting regarding the effect of successful CoA treatment on myocardial strain, and they show different results, depending on type of treatment, follow-up period, and strain evaluation technique (cardiac magnetic resonance, tissue Doppler, 2D speckle tracking, or 3D speckle tracking).…”
Section: Introductionmentioning
confidence: 99%